Exploring we-talk as a relational measure for transformation of motivation in family genetic risk communication - Jingsong Zhao; Yue Guan; Weihua An; Kevin Ward; Colleen M. McBride (SSM: Qualitative Research in Health)
“Transformation of motivation” (TM) and communal coping are interrelated social psychological concepts. TM occurs when an individual’s motivation to protect the self is expanded to include the well-being of important others. TM has largely been assessed by we-talk, that is, counts of the use of we pronouns during conversations about shared experiences. The extent to which we-talk adequately captures TM is underexplored. Family cancer genetic risk communication offers an ideal context for expanded understanding of TM.We conducted think-aloud interviews with 20 ovarian cancer survivors. We assessed counts of we-talk by survivors, matched with qualitative insights describing relational motives for sharing inherited risk information using deductive thematic analysis. A semi-structured interview guide was used to collect data from survivors as they navigated through a website developed to foster family cancer genetic risk communication in real-time. Indicators of relational thinking (i.e. thoughts and feelings) that was prompted during this process were assessed to indicate we-problem- and we-responsibility sentiments.We found that we-talk was used infrequently (1.0 %; SD=0.4) compared to I-talk (8.6 %; SD=1.0), which is consistent with prior studies. We-problem expanded when there was a known family history of cancer but lessened when survivors perceived relatives had competing life priorities. We-responsibility emerged when considering younger relatives but decreased when survivors perceived that it was others’ responsibility to share the information. This is the first study to match pronoun counts with real-time qualitative insights to explore TM. Future studies are needed to further investigate operationalization of TM in relational-motivation research and family-centered interventions.